Tensions within and between religions and human rights - Ven, J. A. van der, 1940-; Ziebertz, Hans-Georg, 1956- (Empirical Research in Religion and Human Rights, 2012)
This volume contains theoretical and empirical articles on tensions within and between religion and human rights. There are conflicts in the past histories of Christianity and Islam in regard to human rights, but also in contemporary history. There are also tensions in the sphere of human rights, like the relation between natural law and human rights, morality and law, liberty and equality, civil rights and socio-economic rights, and more specific ones, like the rights of humans and citizens, religious freedom and the separation of church and state, religious freedom and freedom of speech, and the state and religion on social welfare provisions. The volume aims at theoretical clarification and empirical exploration on data from 14 countries. Contributors include: Jean-Pierre Wils, Piet Hein van Kempen, Mathias Rohe, Johannes (Hans) van der Ven, Anders Sjöborg, Raymond J. Webb, Jack Curran, Marion Reindl, Leo W.J.M. van der Tuin, Clement D. Fumbo, and Hans-Georg Ziebertz.